Postrelease exploration and stress tolerance of landlocked and anadromous Atlantic salmon and their hybrids - Eronen, Aslak; Hyvärinen, Pekka; Janhunen, Matti; Kekäläinen, Jukka; Kortet, Raine (Zenodo, 2023)
Background We studied postrelease explorative behavior and stress tolerance of Landlocked and anadromous Atlantic salmon and their hybrids. For the research, we hybridized the Landlocked salmon of Lake Saimaa with a Baltic anadromous salmon from River Kymijoki, Southern Finland (strain originally from River Neva, Russia). These fish were hybridized in November 2017 and October 2018 in the Kainuu Fisheries Research Station, Paltamo, Kainuu, Finland (kfrs.fi). In the data the fish are treated as four strains (column 'Strain'): 1. Purebred Landlocked salmon (LLxLL), 2. hybrids, where the maternal population was landlocked salmon (LLxBA), 3. hybrids, where the maternal population was Baltic anadromous salmon (BAxLL) and 4. purebred Baltic anadromous salmon (BAxBA). Experiment 1. Post-release exploration In experiment 1., consisting of two separate trials, we studied post-release exploration of the fish in four circular seminatural streams. (Datasets 'Exploration2018.csv' & 'Exploration2020.csv', see also 'Figure_1.jpg') Experiment 2. Stress tolerance In experiment 2. we studied the stress response and recovery of the fish (Dataset 'Stress_BernoulliData.csv', see also 'Figure_2.jpg'). All data is given as .csv-tables (comma separeted values), where ';' serves as separator. They can be opened using e.g. text editor, microsoft excel or R studio. Funding provided by: Academy of Finland Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100002341 Award Number: 308485 Funding provided by: Elinvoimainen Järvilohi ry* Crossref Funder Registry ID: Award Number: Funding provided by: European Maritime and Fisheries Fund Crossref Funder Registry ID: http://dx.doi.org/10.13039/100014510 Award Number: Funding provided by: Maa- ja MetsätalousministeriÖ Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100006697 Award Number: Funding provided by: Natural Resources Institute Finland* Crossref Funder Registry ID: Award Number: Funding provided by: Nordic Centre of Excellence for Sustainable and Resilient ...